1993
DOI: 10.1146/annurev.nu.13.070193.001033
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Mammalian Amino Acid Transport

Abstract: During the last four decades, mammalian amino acid transport systems have been described at the cellular level through general properties such as ion-dependence, kinetics, substrate specificity, regulation of activity, and numerous other characteristics. These studies have allowed the definition of multiple transport systems for neutral, anionic, and cationic amino acids. Each system is distinct but exhibits overlapping substrate specificity. Direct measurement of transport has permitted a wealth of informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(80 citation statements)
references
References 81 publications
8
72
0
Order By: Relevance
“…Because arginine transport is the subject of several reviews over the past few years [163][164][165][166][167][168], we will summarize points most relevant to the present review. In most mammalian cells, arginine requirements are met primarily by uptake of extracellular arginine via specific transporters, such as systems y + , b o,+ , B o,+ or y + L [163,164,168]. Not all transporters are found in every cell type, and activities of specific transporters can be dynamically regulated in response to specific stimuli, such as bacterial endotoxin and inflammatory cytokines [166].…”
Section: Arginine Transportmentioning
confidence: 99%
“…Because arginine transport is the subject of several reviews over the past few years [163][164][165][166][167][168], we will summarize points most relevant to the present review. In most mammalian cells, arginine requirements are met primarily by uptake of extracellular arginine via specific transporters, such as systems y + , b o,+ , B o,+ or y + L [163,164,168]. Not all transporters are found in every cell type, and activities of specific transporters can be dynamically regulated in response to specific stimuli, such as bacterial endotoxin and inflammatory cytokines [166].…”
Section: Arginine Transportmentioning
confidence: 99%
“…To understand the regulation of gene expression by amino acids at a molecular level, we have studied the regulation of CHOP expression in response to leucine limitation because (i) leucine is an essential amino acid that is poorly utilized by cells during a 16-h incubation period (data not shown), (ii) leucine, which is transported by system L, is rapidly equilibrated through the cell membrane (41,42), and (iii) Marten et al (12) have shown that leucine depletion strongly induces CHOP expression. To test the possibility that leucine concentration can influence CHOP expression, HeLa, HepG2, or Caco-2 cells were incubated for 16 h in medium containing different concentrations of leucine.…”
Section: Induction Of Chop Mrna Expression By Leucine Limitation-mentioning
confidence: 99%
“…3) Reconstitution experiments in Xenopus oocytes have demonstrated that the dependence of nitrite production by transfected NOS2 is dependent upon co-transfection and expression of the CAT transporters. 3 4) While other transport systems have been defined in physiologic terms (60,85), the only other cationic amino acid transporters cloned and sequenced to date, D2 (86) and 4F2 (87), are unlikely to have contributed to L-arginine uptake in our cells. D2 expression is limited to the kidney and intestine (86), and the 4F2 transporter has one-tenth the activity of the CAT family of transporters and could not account for the kinetic data in this report (87).…”
Section: Figmentioning
confidence: 99%